Biodegradable Plastic from Cassava and Organic Acid as a Synthetic Plastic Replacement - Aji Ridho Pangestu; Raifa Tryas Shara; Zahrul Mufrodi (Universitas Ahmad Dahlan, 2019)
Currently plastic has been widely used for various purposes of packaging food and beverages. The use of synthetic plastic is increasingly then become a waste that cannot be degraded and pollute the environment. In Southeast Asia generates 379.198 million tons of plastic waste per year, meanwhile, Indonesia became the first contributor to the largest plastic waste producer which is 187.2 million tons per year. Biodegradable plastic can be an alternative the eco-friendly and easily degraded packaging materials as one way to replaced synthetic plastic. Cassava flour could utilized to make biodegradable plastic with cassava starch content reach 81.6 %. The addition of sorbitol plasticizer is as a giver of elastic properties to the material and chitosan as an amplifier and antimicrobial. The variation of weight ratio in gram that used is organic acids 50(1), 60(2), and 70(3). The variation of sorbitol are 3(A), 6(B), and 9(C). The variation of chitosan are 1(i), 3(ii), and 5(iii). The organic acids used are apple vinegar and rice vinegar with 2% acetic acid as a comparison. The research procedure begins with making cassava starch, making a film of biodegradable plastic, and sample testing. The film of biodegradable plastic has performed by tensile strength test analysis, elongation at break test, and biodegradable test. The results showed that the highest of percent biodegradable is on 2Ci with the results is 64.58%. The best of mechanical properties reached by using apple vinegar with the results of tensile strength is 105.98 kg/cm2 and elongation at break is 129.91%.